IMPLEMENTASI EKSISTENSIAL HUMANISTIK DENGAN TEHNIK MODELING UNTUK MENINGKATKAN EMPATI PADA MAHASISWA - Alma Yulianti Yulianti; Yeni Karneli (Jurnal Al-Fatih, 2019)
Empathy makes students able to see themselves, more aware of and pay attention to the roles and perspectives of others regarding an issue and empathy is one of important social skills in life. The quality of social relationships that are formed allows individuals to create and develop a recognition of the existence and understanding of themselves in a healthy way to organize and carry out an action in order to achieve an expected goal, that you can complete tasks and demands as expected. The research was aimed to: (1) find conditions of empathy and to students; (2) find group guidance with effective modeling techniques to increase empathy for students. These indicators, including outreach, shelter home, group together (support group), support groups), home visits, and mentoring programs that are carried out using the principle of acceptance as unconditional positive regard. The modeling techniques as a humanistic existential implementation and the application of this technique able to increase empathy among students.